Handbook of Nordic new religions - Lewis, James R.; Tøllefsen, Inga Bårdsen. (Brill Handbooks on Contemporary Religion, 2015)
When James R. Lewis, one of the editors of the current collection, first moved to Norway in late 2009, he was unprepared to discover that so many researchers in Nordic countries were producing innovative scholarship on new religions and on the new age subculture. In fact, over the past dozen years or so, an increasingly disproportionate percentage of new religions scholars have arisen in Nordic countries and teach at universities in Denmark, Finland, Norway, Sweden and the Baltic countries. Nordic New Religions, co-edited with Inga B. Tøllefsen, surveys this rich field of study in this area of the world, focusing on the scholarship being produced by scholars in this region of northern Europe.